1983
DOI: 10.1111/j.1600-0765.1983.tb00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of prostaglandin E2, thromboxane, and prostacyclin in periodontal tissues

Abstract: Prostaglandin E2 (PGE2), thromboxane A2 (TXA2), and prostacyclin (PGI2) are naturally occurring metabolites of arachidonic acid which have been associated with inflammation. To assess the relative importance of these mediators in periodontal diseases, the levels of all three were measured by radioimmunoassay in human tissues removed during surgery. TXA2 and PGI2 were determined as their stable hydrolysis products thromboxane B2 (TXB2) and 6‐keto‐prostaglandin F1α (6‐K‐PGF1α), respectively. Tissues from periodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 32 publications
2
31
2
Order By: Relevance
“…This suggests that there is an activation process which enhances tis-sue CO activity. Furthermore, inflamed periodontal tissues which are undergoing attachment loss and bone resorption contain elevated levels of CO products, particularly PGE 2 and to a lesser extent, thromboxane A2 (TxA2) [7][8][9]. Finally, there are considerable data which demonstrate that drugs which block ARA metabolism serve to both diminish the levels of CO products present within the periodontal tissues and inhibit periodontal inflammation, attachment loss and bone resorption [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that there is an activation process which enhances tis-sue CO activity. Furthermore, inflamed periodontal tissues which are undergoing attachment loss and bone resorption contain elevated levels of CO products, particularly PGE 2 and to a lesser extent, thromboxane A2 (TxA2) [7][8][9]. Finally, there are considerable data which demonstrate that drugs which block ARA metabolism serve to both diminish the levels of CO products present within the periodontal tissues and inhibit periodontal inflammation, attachment loss and bone resorption [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Levels of PGE 2 are elevated in the gingival tissue and gingival fluid of patients with periodontitis, compared with periodontally healthy subjects. [2][3][4][5] It has also been reported that the inhibition of PGE 2 using selective or nonselective nonsteroidal anti-inflammatory drugs decreases periodontal disease progression and reduces alveolar bone resorption, which highlights the significance of PGE 2 in the pathogenesis of periodontal disease. 6 -8 In addition to these findings, bone resorption in lipopolysaccharide-treated mice has been shown to be dependent on PGE 2 synthesis, a finding that might be explained by the observation that PGE 2 stimulates the formation of osteoclasts.…”
mentioning
confidence: 99%
“…Therefore, the presence of elevated GCF-PGE 2 levels in periodontal tissues undergoing active inflammatory destruction may represent a potential diagnostic concept for the determination of disease activity. In addition to PGE 2 , the levels of TxB 2 and 6-keto-prostaglandin F 1α were measured in human biopsies adjacent to shallow and deep periodontal pockets [50]. Control gingival samples were gained from retromolar distal wedge samples that did not yield clinical evidence of periodontal inflammation.…”
Section: B Arachidonic Acid Metabolite Levels In Periodontal Tissuesmentioning
confidence: 99%